The Physically Nonlinear Analysis of Circular Plate on Deformable Foundation - Valentinas Jankovski; Valentinas Skaržauskas (The Baltic Journal of Road and Bridge Engineering)
A circular reinforced concrete plate on deformable foundation is investigated. The foundation is composed of three layers of soil which are defined as isotropically nonlinear materials with variable physical properties. The reinforced plate is treated as an elastic body. The plate is subjected to dissymmetrical half-circular loading of linearly variable pressure. Generally, the unified system “structure-foundation” is the contact analysis problem, which is modeled by ANSYS software. Plastic shear deformations are evaluated by solving the contact problem by the finite element method. The comparative analysis, including the treatment of physically linear system “structure-foundation”, is performed. The comparison based on linear analysis shows that rigidity of the foundation generates higher extreme stresses in the plate in terms of the Huber-Mises criterion. However, in nonlinear analysis, the intensity of stresses is naturally decreasing, when a more flexible model of the foundation is used.